Management of otosclerosis with obliterated footplate and round window involvement - Harim Priyono; Anita Amalia Sari; Semiramis Zizlavsky; Widayat Alviandi; Respati W. Ranakusuma (PERHATI-KL, 2022)
ABSTRACTBackground: Otosclerosis with obliterated footplate describes a condition with an overgrowth of bone so that the oval window is almost indistinguishable from the surrounding area. The occurence of round window obliteration is uncommon. In such cases, surgery is more difficult to perform and the results are often unsatisfactory. Purpose: To find out the management option for obliterative otosclerosis. Case report: A 35-year-old-man with suspected bilateral otosclerosis. The patient underwent transcanal endoscopic stapes surgery of the left ear with large fenestra stapedotomy procedure. Clinical question: In adult patients with obliterative otosclerosis, does stapes surgery improve hearing function and reduce complication? Review method: Using PubMed, EBSCOhost, Scopus and Proquest to search for the evidence of randomised control trial (RCT), cohort and case-control studies. Critical appraisal was conducted using critical appraisal tools from Center for Evidence Based Medicine (CEBM), Oxford University and qFAITH for systematic review/meta-analysis. Result: The literature searching used eligibility criteria based on keywords from clinical question found one study regarding the evaluation of intra-operative factors in otoslecrosis surgery outcomes, which was relevant to our clinical question. Conclusion: Large fenestra stapedotomy or stapedectomy is the preferred surgical technique for the management of obliterative otosclerosis. The involvement of round window caused a sensorineural hearing loss (SNHL) component and has a worse prognosis of hearing outcome post operatively. A further study is required to assess the best management for obliterative otosclerosis. ABSTRAKLatar belakang: Otosklerosis dengan obliterasi footplate menggambarkan suatu kondisi pertumbuhan tulang yang berlebihan sehingga tingkap lonjong hampir tidak dapat dibedakan dengan daerah sekitarnya. Obliterasi sampai ke tingkap bundar jarang terjadi. Hal tersebut menyebabkan operasi lebih sulit dilakukan dan hasilnya seringkali tidak memuaskan. Tujuan: Untuk mengetahui pilihan tatalaksana otosklerosis obliteratif. Laporan kasus: Laki-laki 35 tahun dengan suspek otosklerosis bilateral. Pasien menjalani operasi stapes telinga kiri dengan pendekatan endoskopi transkanal menggunakan prosedur stapedotomi fenestra besar. Pertanyaan klinis: Pada pasien dewasa dengan otosklerosis obliteratif, apakah operasi stapes dapat memulihkan fungsi pendengaran dan mengurangi komplikasi? Telaah literatur: Pencarian bukti melalui database PubMed, EBSCOhost, Scopus dan Proquest. Untuk uji coba kontrol acak, kohort dan studi kasus-kontrol, penilaian kritis dilakukan dengan menggunakan penilaian kritis dari CEBM, Oxford University dan qFAITH untuk tinjauan sistematis/meta-analisis. Hasil: Penelusuran literatur berdasarkan kriteria dari pertanyaan klinis, didapati satu artikel mengenai evaluasi faktor-faktor intraoperatif yang relevan dengan pertanyaan klinis. Kesimpulan: Stapedotomi fenestra besar atau stapedektomi adalah teknik bedah yang lebih dipilih untuk tatalaksana otosklerosis obliteratif. Keterlibatan tingkap bundar menyebabkan komponen gangguan pendengaran sensorineural, dan memiliki prognosis hasil pendengaran pasca operasi yang kurang baik. Dibutuhkan studi lebih lanjut untuk menilai tentang penatalaksanaan terbaik untuk kasus otosklerosis obliteratif.